Exploring the Influence of Digital Remote Platforms on Learners' Speaking Abilities in Educational Contexts - Hafriana, Noerhaetty; Yahya Himni, M. Saleh; Joemar Minoza (Institut Agama Islam Negeri Parepare, 2026)
This study examines the influence of remote learning environments on students’ speaking abilities, particularly among learners in geographically isolated areas. Using a descriptive qualitative design, data were collected from 50 ninth-grade students at a private Islamic junior secondary school in a remote area through classroom observations, semi-structured interviews with English teachers, and self-report questionnaires focusing on linguistic competence and motivation. The findings indicate that remote learning contexts intensify several barriers to speaking development, including limited vocabulary, poor pronunciation, low confidence, and reduced motivation. These challenges are largely attributed to minimal exposure to authentic English use, strong interference from the first language, and restricted learning environments. In addition, psychological factors such as fear of making mistakes and classroom interaction constraints further hinder students’ oral performance. The study also identifies gaps in instructional implementation, including limited evaluation practices and time constraints, which contribute to less effective learning outcomes. These findings highlight the importance of providing targeted pedagogical support, improving access to digital learning resources, and adopting culturally responsive teaching strategies to enhance students’ speaking proficiency in remote settings. This study contributes to the broader discussion on equitable English language education in underserved areas.